Comparison of Direct and Extraction Immunoassay Methods With Liquid Chromatography-Tandem Mass Spectrometry Measurement of Urinary Free Cortisol for the Diagnosis of Cushing’s Syndrome - Mu, Danni; Fang, Jiadan; Yu, Songlin; Ma, Yichen; Cheng, Jin; Hu, Yingying; Song, Ailing; Zhao, Fang; Zhang, Qi; Qi, Zhihong; Zhang, Kui; Xia, Liangyu; et al. (Annals of laboratory medicine, 2024)
Twenty-four-hour urinary free cortisol (UFC) measurement is the initial diagnostic test for Cushing's syndrome (CS). We compared UFC determination by both direct and extraction immunoassays using Abbott Architect, Siemens Atellica Solution, and Beckman DxI800 with liquid chromatography-tandem mass spectrometry (LC-MS/MS). In addition, we evaluated the value of 24-hr UFC measured by six methods for diagnosing CS.BackgroundTwenty-four-hour urinary free cortisol (UFC) measurement is the initial diagnostic test for Cushing's syndrome (CS). We compared UFC determination by both direct and extraction immunoassays using Abbott Architect, Siemens Atellica Solution, and Beckman DxI800 with liquid chromatography-tandem mass spectrometry (LC-MS/MS). In addition, we evaluated the value of 24-hr UFC measured by six methods for diagnosing CS.Residual 24-hr urine samples of 94 CS and 246 non-CS patients were collected. A laboratory-developed LC-MS/MS method was used as reference. UFC was measured by direct assays (D) using Abbott, Siemens, and Beckman platforms and by extraction assays (E) using Siemens and Beckman platforms. Method was compared using Passing-Bablok regression and Bland-Altman plot analyses. Cut-off values for the six assays and corresponding sensitivities and specificities were calculated by ROC analysis.MethodsResidual 24-hr urine samples of 94 CS and 246 non-CS patients were collected. A laboratory-developed LC-MS/MS method was used as reference. UFC was measured by direct assays (D) using Abbott, Siemens, and Beckman platforms and by extraction assays (E) using Siemens and Beckman platforms. Method was compared using Passing-Bablok regression and Bland-Altman plot analyses. Cut-off values for the six assays and corresponding sensitivities and specificities were calculated by ROC analysis.Abbott-D, Beckman-E, Siemens-E, and Siemens-D showed strong correlations with LC-MS/MS (Spearman coefficient r=0.965, 0.922, 0.922, and 0.897, respectively), while Beckman-D showed weaker correlation (r=0.755). All immunoassays showed proportionally positive bias. The areas under the curve were 0.975 for Abbott-D, 0.972 for LC-MS/MS, 0.966 for Siemens-E, 0.948 for Siemens-D, 0.955 for Beckman-E, and 0.877 for Beckman-D. The cut-off values varied significantly (154.8-1,321.5 nmol/24 hrs). Assay sensitivity and specificity ranged from 76.1% to 93.2% and from 93.0% to 97.1%, respectively.ResultsAbbott-D, Beckman-E, Siemens-E, and Siemens-D showed strong correlations with LC-MS/MS (Spearman coefficient r=0.965, 0.922, 0.922, and 0.897, respectively), while Beckman-D showed weaker correlation (r=0.755). All immunoassays showed proportionally positive bias. The areas under the curve were 0.975 for Abbott-D, 0.972 for LC-MS/MS, 0.966 for Siemens-E, 0.948 for Siemens-D, 0.955 for Beckman-E, and 0.877 for Beckman-D. The cut-off values varied significantly (154.8-1,321.5 nmol/24 hrs). Assay sensitivity and specificity ranged from 76.1% to 93.2% and from 93.0% to 97.1%, respectively.Commercially available immunoassays for measuring UFC show different levels of analytical consistency compared to LC-MS/MS. Abbott-D, Siemens-E, and Beckman-E have high diagnostic accuracy for CS.ConclusionsCommercially available immunoassays for measuring UFC show different levels of analytical consistency compared to LC-MS/MS. Abbott-D, Siemens-E, and Beckman-E have high diagnostic accuracy for CS.